Relationship of silver fir (Abies alba Mill.) mortality in the area of Fužine with climatic and structural parameters : Povezanost mortaliteta obične jele (Abies alba Mill.) na području Fužina s klimatskim i strukturnim parametrima - Ugarković, Damir (Array, 2021)
Tree dieback is a complex process involving negative impact of various abiotic, biotic and anthropogenic factors. Climate change, comprising all those effects, is generally considered as the largest threat to forest ecosystems in Europe. Although the scale of climate change impacts on forests is not yet fully understood, especially on the regional or species level, significant damage seems to be caused by weather extremes, such as drought and strong winds. With the expected increase in the number, length, and/or intensity of extreme weather events in Croatia, research into the causes of tree mortality is both important and timely. Silver fir is the most damaged and endangered conifer tree species in Croatia. The dieback of silver fir can be attributed to various factors, therefore the goals of this research were to determine the mortality of silver fir trees (by number and volume) for various causes of mortality, among which the climatic and structural parameters were of most interest. The twenty-year data for tree mortality in pure silver fir stands in the area of Fužine (Gorski kotar, Croatia) were collected and analysed. The largest number and volume of dead trees was caused by complex (multiple causes) dieback in the overstorey (0,75 N/ha, 2,35 m3/ha), and the smallest (0,17 N/ha, 0,02 m3/ha) by dieback of supressed trees. No significant differences were determined regarding the timing of tree death for different causes of mortality. Climatic parameters (drought, air temperature, PET) and structural parameters of the stands (tree DBH, social position, crown diameter, shading, physiological maturity) as well as plot inclination were found to be the factors of a significant influence on the mortality of silver fir trees.